Antioxidative and anti-inflammatory effects of high beta-glucan concentration purified aqueous extract from oat in experimental model of LPS-induced chronic enteritis. (April 2015) - Suchecka, D.; Harasym, J.P.; Wilczak, J.; Gajewska, M.; Oczkowski, M.; Gudej, S.; Błaszczyk, K.; Kamola, D.; Filip, R.; Gromadzka-Ostrowska, J.
Highlights: Low molecular weight beta-glucan caused reduction in plasma lipid peroxidation of healthy animals. Oat beta-glucan of different MW exhibits anti-inflammatory and antioxidative activity in vivo. Dietary high and low MW beta-glucans decreased the number of blood total lymphocytes T, B and Tc. High MW beta-glucan decreased plasma 25-dihydroxycholesterol and TBARS in control animals. Dietary high and low MW oat beta-glucans decreased blood SOD activity in LPS-induced enteritis rats. Abstract: Contrary to most of studies concerning oat beta-glucan activity using non-purified oat milling fraction this study investigates aqueous extract of beta-glucan from oat (purity approx. 75%) with high (G1) and low (G2) molecular weight to verified its anti-inflammatory and antioxidant effects in a model of chronic LPS-induced enteritis . Chronic inflammatory bowel diseases, e.g . Crohn's disease (CD) and ulcerative colitis (UC) are expanding with the highest annual CD incidence in North America and the highest annual UC occurrence in Europe. The study has been conducted on Spraque-Dowley rats fed diets supplemented with 1% of G1 or G2 beta-glucan. Obtained results revealed that supplementation with both beta-glucan fractions led to significant reduction of different type blood leucocytes (lymphocytes T and B, granulocytes and lymphocytes Tc). Higher reduction of lipid peroxidation was observed in healthy rats after G1 supplementation, while G2 led this reduction in enteritis groups, mainly due to the increase of antioxidative defense.